Pengaruh Literasi Keuangan Terhadap Perilaku Konsumtif dan Locus of Control Pada Penggunaan Shopee Paylater - Ani, Heti Nur; Belinda, Presti; Mahmudah, Annita; Indira, Irma (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine the effect of Financial Literacy on Consumptive Behavior Through Locus Of Control in Using Shopee Payleter in Millennial Generation (Study on University Students in Lamongan). The object of this research is all the millennial generation or university students in Lamongan. The sample in this study were students majoring in Accounting class of 2019 and 2020 at universities in Lamongan. This study uses primary data by distributing questionnaires online to 100 respondents using the solvin formula, which is a university millennial generation in Lamongan aged 22-40 years and is a Shopee Paylater user. This study uses the technique of Probability Sampling with Simple Random Sampling Technique. This study uses the Partial Least Square (PLS) approach using the SmartPLS Version 3.0 application. The results showed that financial literacy has a significant effect on the consumptive behavior of shopee paylater users with a positive relationship direction. Financial literacy has a significant effect on the locus of control of shopee paylater users with a positive relationship direction. Locus of control has a significant effect on the consumptive behavior of shopee payleter users. can mediate the relationship of financial literacy to the consumptive behavior of Shopee Paylater users with a positive relationship direction.